Targeted germline sequencing of patients with three or more primary melanomas reveals high rate of pathogenic variants. Issue 3 (June 2020) - Li, Christopher; Liu, Tong; Tavtigian, Sean V.; Boucher, Kenneth; Kohlmann, Wendy; Cannon-Albright, Lisa; Grossman, Douglas
Abstract : Individuals with multiple primary melanomas have rates of germline CDKN2A pathogenic variants of 3%–18%, and are also frequent carriers of variants in the melanocortin-1 receptor. Few patients with numerous (≥ 3) primary melanomas have been studied with respect to these or other potential germline pathogenic variants. We investigated 46 patients with ≥ 3 primary melanomas (3, n = 17; 4, n = 14; 5–14, n = 15) to determine if higher rates of germline pathogenic variants of CDKN2A, MC1R, or other cancer genes could explain their extreme melanoma phenotype. Most (43/46, 93%) patients had variants in MC1R and 11/46 (24%) had CDKN2A pathogenic variants, but only male sex and having two variants in MC1R correlated with increasing number of melanomas. Panel screening of 56 other cancer predisposition genes did not reveal other germline pathogenic variants associated with melanoma ( CDK4, BAP1, POT1 ), although pathogenic variants in TP53, CHEK2, and BRCA2 were present in three separate patients and some patients had variants of uncertain significance. In summary, targeted germline sequencing of patients with ≥ 3 primary melanomas revealed a high rate of pathogenic variants in CDKN2A and other known cancer genes. Although further investigation of these pathogenic variants and variants of uncertain significance is needed, these results support cancer gene panel testing in individuals diagnosed with ≥ 3 melanomas. Abstract : Supplemental Digital Content is available in the text.